(3GdCNHGQ GdefKhQI GdeQhjIs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3EPG GdeGd de jhLH Ydjc YWGA MbjbI Jbhi Ch Ndjd JNGdbg s
(3BNQgG (B:s
(3CNHQfG CHhYKeGf bGd(B: (3CNHQfG GdYJHi bGd(B: (3ONd SYjO Hf YJHGf abGd jGCejQ GdeDefjf(B: (3Efj CQjO Cf CUac HUaJc aQH LhGO YKQ aj CTfGaI hcHG aj ejOGfg aQMe Gddg YHOkG s
(3GfXQ GdLRA GdChd HQbej (B11s
12 (3COH HYfhGf CNHGQ CHj HcQ Hf OQjOs
(3ChQGb eJaQbI ef GdLRFjf GdQGHY hGdNGeS ef GdcJGH gcPG cJH Ydjg GdTjN WGgQ GdLRGFQj QMeg Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B8 s
Keywords: (3GdCOHs